Distinct maturation, glucose metabolism, and inflammatory function of human monocytes-derived IDECs mediated by anti-IgE and Pam3CSK4 alone or in combination - Gao, Cuie; Zhao, Ying; Ge, Lan; Liu, Wenying; Zhang, Mengjie; Ni, Bing; Song, Zhiqiang (Frontiers in Immunology, 2024)
Background Cell energy metabolism controls the activation and function of dendritic cells (DCs). Inflammatory dendritic epidermal cells (IDECs) in skin lesions of atopic dermatitis (AD) express high-affinity IgE receptor (FcϵRI) and toll-like receptor 2 (TLR2), which mediate the generation and maintenance of inflammation. However, cellular energy metabolism and effector function of IDECs mediated by FcϵRI and TLR2 have not been fully elucidated. Methods IDECs in vitro were treated with TLR2 agonist Pam3CSK4 and anti-IgE alone or in combination for 24 h. Further, we analyzed the expression of cell surface activation markers, production of inflammatory factors, and cellular energy metabolism profiles of IDECs by using flow cytometry, multiplex assay, RNA sequencing, targeted energy metabolism, and seahorse assays. Results Compared to the unstimulated or anti-IgE groups, Pam3CSK4 alone or combined with anti-IgE groups significantly increased the expression of CD80, CD83, and CD86 on IDECs, but did not affect the expression of the above markers in the anti-IgE group. The release of inflammatory cytokines increased in the Pam3CSK4 alone or combined with anti-IgE groups, while there was a weak increasing trend in the anti-IgE group. The glycolysis/gluconeogenesis pathway of carbon metabolism was affected in all treatment groups. Furthermore, compared to the control group, we found a decrease in pyruvic acid, upregulation of PFKM, downregulation of FBP1, and increase in extracellular lactate, glycolysis rate, and glycolysis capacity after all treatments, while there was no difference between each treatment group. However, there was no difference in glycolytic reserve and mitochondrial basic and maximum respiration among all groups. Conclusion Our results indicate that glycolysis of IDECs may be activated through FcϵRI and TLR2 to upregulate inflammatory factors, suggesting that danger signals from bacteria or allergens might evoke an inflammatory response from AD through the glycolysis pathway.